KEBIJAKAN FISKAL NEGARA INDONESIA DALAM PERSPEKTIF EKONOMI ISLAM - Supangat, Supangat (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2013)
As part of theÂ muâamalah discourse, fiscal policy in Islam is flexible and open to ijtihad. Texts related to fiscal policy can not be separated from the socioÂ historical circumstances early Islamic society. Interpretation must use a contextual approach, although the mechanism may be different contextualisation. With the above formulation, this studyÂ found in common principles and objectives of the Stateâs fiscal policy in Indonesia. In fact, some types of taxes collected by the government is a reformulation of the tax that is applied in the early days of Islam. Thus, the system of fiscal policies during the State of Indonesia is still in the corridors of Shariâah. However, implementation of such systems is still far from the expected. With the point of the equation, the government can implement fiscal policies of an Islamic state in accordance with the laws and culture of Indonesia. In this paper, the authors propose the idea to the admissibility of zakat and taxation as a source of state revenue.